2021
DOI: 10.3389/fvets.2021.751861
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid Promoting B Lymphocyte Differentiation and Anti-epithelial Cells Apoptosis Mediate the Protective Effects of Hermetia illucens Feed in ETEC Induced Piglets Diarrhea

Abstract: Newborn piglets are prone to diarrhea after weaning as a result of changes in their environment and feed. Enterotoxigenic Escherichia coli (ETEC) K88 strain is a typical pathogen that causes diarrhea in such stage of piglets. Hermetia illucens larvae are widely used in livestock and poultry production because of their high nutritional value and immunoregulatory effects. This study aimed to evaluate the protective effects of H. illucens feed in protecting against ETEC induced diarrhea in piglets and to unravel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that the addition of organic acids such as citric acid could improve food flavor, maintain its nutritional value, and extend its shelf life [15]. At the same time, it can increase the feed intake in piglets and poultry and improve growth efficiency [16,17]. In addition, recent research has shown that citric acid can enhance the uptake of heavy metals and other substances by plants [18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the addition of organic acids such as citric acid could improve food flavor, maintain its nutritional value, and extend its shelf life [15]. At the same time, it can increase the feed intake in piglets and poultry and improve growth efficiency [16,17]. In addition, recent research has shown that citric acid can enhance the uptake of heavy metals and other substances by plants [18].…”
Section: Introductionmentioning
confidence: 99%